Dental Articulator – Hanau Wide Vue - Monika.D1 , Sanjna Nayar 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The articulator plays an important role in Dentistry, since it allows adequate diagnosis and treatment planningto promote the oral health of our patients. The Semi adjustable, Fully adjustable articulator reduces theintervention of Prosthodontists; when well employed, it simplifies the daily clinical routine, reducing thenumber of sessions, chair time and need of interventions in the patient’s mouth, besides allowing moreaccurate procedures, consequently without damages to the stomatognathic system.Dental articulatorsare instruments that reproduce jaw movements to varying degrees of accuracy. This article aims to give anoverview of Hanau wide vue and describe their applications and limitations.